2020
DOI: 10.3390/md18060302
|View full text |Cite
|
Sign up to set email alerts
|

Light-Mediated Toxicity of Porphyrin-Like Pigments from a Marine Polychaeta

Abstract: Porphyrins and derivatives form one of the most abundant classes of biochromes. They result from the breakdown of heme and have crucial physiological functions. Bilins are well-known representatives of this group that, besides significant antioxidant and anti-mutagenic properties, are also photosensitizers for photodynamic therapies. Recently, we demonstrated that the Polychaeta Eulalia viridis, common in the Portuguese rocky intertidal, holds a high variety of novel greenish and yellowish porphyrinoid pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In fact, Eulalia is a known intertidal active forager that seeks shelter from direct sunlight underneath mussel beds [ 19 ]. Recent evidence of photoactivation of pigment extracts, especially the yellow pigments from the proboscis, which bear the clearest hallmarks of a porphyrinoid nature, also indicates roles as biocides and potentially even as part of a light-sensing arrangement [ 23 ]. We emphasize the yellowish pigment termed Pr2 (from the proboscis) as target for subsequent research due to its abundance, plus its clearer Soret and Q bands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Eulalia is a known intertidal active forager that seeks shelter from direct sunlight underneath mussel beds [ 19 ]. Recent evidence of photoactivation of pigment extracts, especially the yellow pigments from the proboscis, which bear the clearest hallmarks of a porphyrinoid nature, also indicates roles as biocides and potentially even as part of a light-sensing arrangement [ 23 ]. We emphasize the yellowish pigment termed Pr2 (from the proboscis) as target for subsequent research due to its abundance, plus its clearer Soret and Q bands.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Hediste diversicolor , which is known for its widely variable pigmentation pattern [ 18 ], tetrapyrroles in Eulalia constitute its primary coloration. Most importantly, D’Ambrosio et al [ 23 ] revealed photodynamic properties in Eulalia ’s tetrapyrrolic pigments, which, together with the wide range of pigments, makes the worm (and likely other Polychaeta) a promising target for bioprospecting for novel photosensitizers. Photosensitizer pigment synthesis in vitro is a laborious and costly endeavor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One valve was used as a test sample ( N. lapillus extracts diluted in PBS, as described above), and the other was used as its respective control (PBS only). For all crude extracts, the test valve was exposed to 1 mL of D1 or D2 dilutions, corresponding to 1 mg/mL and 0.5 mg/mL total protein, respectively, while the control was treated with 1 mL of PBS [ 39 ]. Test valves and controls were assayed for 1 h and processed immediately afterwards for subsequent histopathological analysis (as described above) and comet assay.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, systemic administration of traditional photosensitizers results in their spread throughout the whole body since most of the traditional photosensitizers have no specificity against cancer cells and non-specific accumulation in the whole body [ 13 ]. Due to these problems, normal tissues and/or skin frequently exposed to burning and/or pigmentation require that patients avoid sunlight for a long time [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%